The frequency of bottle feeding as the main factor of baby bottle tooth decay syndrome - Mochamad Fahlevi Rizal; Heriandi Sutadi; Boy M Bachtiar; Endang W Bachtiar (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2010)
Background: Dental caries remains as main problem in Indonesia and its prevalence is high (90.05%). However, there is no appropriate data that can be used to analyze dental caries in toddlers, especially baby bottle tooth decay syndrome (BBTD), though the number of BBTD cases is high in some pediatric dental clinics (90% of patients visiting the clinics). Even though some factors have already been considered to be the risk factor of BBTD, the main risk factor of BBTD is still unknown, especially BBTD in Indonesia. Purpose: This research was aimed to obtain data relating with bottle-feeding habit in 3-5 year old children in Indonesia and its caries risk. Method: The study was an observational research conducted with clinical examination through caries status (deft) of each child deserved by pediatric dentists and through questionnaire distributed to parents to examine the risk factor of BBTD. Observation was conducted on 62 children in the range of age 3 to 5 years old with bottle-feeding habit. Result: The results revealed that status of caries was various. The data showed that the frequency of bottle feeding more than twice could trigger BBTD 2.27 times higher than other factors such as the use of bottle feeding as a pacifier prior sleeping, the period of bottle-feeding, and the breast-feeding experience. Conclusion: though milk as subtract can possibly become a factor triggering caries, the frequency of bottle-feeding is highly considered as main factor. Since it could modulated the bacterial colonization on dental surface, which affects its virulence.Latar belakang: Karies masih menjadi masalah utama di Indonesia. Dalam praktek sehari-hari prevalensi karies masih sangat tinggi (90.05%). Belum ada data yang memadai dalam penelaahan karies yang spesifik pada anak balita selama ini khususnya kasus sindroma karies botol (SKB) sementara itu kasus SKB ditemukan sangat tinggi di beberapa klinik gigi anak (90% dari jumlah pasien yang datang ke klinik). Beberapa faktor menjadi resiko kejadian SKB dan belum diketahui faktor resiko utama kejadian karies khususnya di Indonesia. Tujuan: Penelitian ini dilakukan guna mendapatkan data yang berhubungan dengan kebiasaan minum susu botol pada anak usia 3-5 tahun di Indonesia serta resiko kejadian karies yang ditimbulkannya. Metode: Penelitian ini merupakan penelitian observasional yang dilakukan dengan metode pemeriksaan klinis melalui pencatatan status karies (deft) setiap anak oleh dokter gigi anak serta pengisian kuesioner yang dilakukan oleh orang tua untuk menentukan faktor resiko kejadian SKB. Pengamatan dilakukan pada 62 orang anak usia 3-5 tahun yang mempunyai kebiasaan minum susu botol sesuai dengan kriteria inklusi. Hasil: Hasil pemeriksaan klinis dan kuesioner memberikan gambaran status karies yang bervariasi. Data yang didapat dari penelitian ini menjelaskan, bahwa frekuensi minum susu botol lebih dari dua kali menyebabkan SKB 2.27 kali lebih besar dibandingkan dengan beberapa faktor lain, seperti menjadikannya pengantar tidur, lamanya mengonsumsi, dan riwayat minum ASI. Kesimpulan: Susu sebagai subtrat mungkin dapat dijadikan alasan kejadian karies akan tetapi yang menjadi resiko utama kejadian adalah frekuensi konsumsi susu botol itu sendiri. Kondisi ini dapat dihubungkan dengan modulasi substrat terhadap perkembangan kolonisasi bakteri di permukaan gigi, sehingga secara tidak langsung juga mempengaruhi virulensinya.